Speciation and evolution of growth form in Adesmia D. C. (Dalbergieae, Fabaceae): the relevance of Andean uplift and aridification - Pérez, Fernanda; Lavandero, Nicolás; Hinojosa, Luis Felipe; Cisternas, Mauricio; Araneda, Daniela; Pinilla, Nicolás; Moraga, Valeska (Frontiers in Plant Science, 2024)
The Andean uplift and the concomitant aridification drove the rapid diversification of several plant lineages that were able to colonize warmer and drier habitats at low elevations and wetter and colder habitats at high elevations. These transitions may be facilitated by shifts in plant strategies to cope with drought and cold, which in turn can trigger episodes of accelerated species diversification. Here, we used four nuclear DNA markers to infer phylogenetic relationships of 80 Adesmia species of annuals, perennial herbs, shrubs and small shrubs that occur in Chile and Argentina. We reconstructed ancestral states for area, climatic niche and growth form to explore how Andean uplift and aridification promoted Adesmia diversification. We also performed logistic and linear regression analyses between different components of growth form (life span, woodiness and plant height) and climate.. Finally, we estimated speciation rates across the phylogeny. Our results suggest that the ancestor of Chilean Adesmia was a perennial herb that probably originated in the high Andes of northern and central Chile. The low elevations of Central Chile were colonized in the late Miocene, whereas the high latitudes of Patagonia and the hyperarid coastal Atacama Desert were colonized repeatedly since Pliocene by lineages with different growth forms. Multiple and bidirectional transitions between annual and perennial habits and between herbaceous and woody habits were detected. These shifts were not correlated with climate, suggesting that the different growth forms are alternative and successful strategies to survive unfavorable seasons of both desert and high Andes. Net diversification analysis indicated a constant rate of diversification, suggesting that the high species diversity of Adesmia that occur in Chile is due to a uniform speciation process rather than to accelerated episodes of speciation.